DO ACCOUNTING STANDARDS EXPLAIN DIFFERENCES IN EARNINGS-PRICE RATIOS OF JAPANESE AND U.S. FIRMS? - Indra Wijaya Kusuma (Journal of Indonesian Economy and Business (JIEB), 2005)
This study examines the variation in earnings-price ratios across Japanese and U.S.firms. Previous literature documents that Japanese firms have consistently lower earnings-price ratios than U.S. firms. The differences in earnings-price ratios have been primarilyattributed to differences in Japanese and U.S. accounting standards. However, Aron(1991)and French and Poterba (1991) provided a conflicting evidence on the argument ofaccounting standards that are the only cause of the differences in earnings-price ratios Theobjective of this study is to examine the issue that Japanese firms lower earnings priceratios is attributable to the differences in the accounting standards..The results show that adjusting Japanese earnings does not entirely eliminate thedifferences in the earnings-price ratios between Japanese and U.S. firms. On the average,the accounting standard differences account for 52 percent of the differences in theaverage earnings-price ratios of Japanese and U.S. firms.Controlling for differences in accounting standards does not eliminate the differences inthe earnings-price ratios of the Japanese and U.S. firms. It is appropriate to conclude thatalthough differences in accounting standards occur between Japanese and U.S. firms, it isnot the only factor that contributes to the differences in the earnings-price ratios ofJapanese and U.S. firmsKeywords: Earnings price ratio, Japanese earnings adjustment, U.S. firms, Japanese firms.